PENGARUH IMPLEMENTASI GOOD GOVERNANCE DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS KINERJA LAPORAN KEUANGAN PEMERINTAH DAERAH DI KABUPATEN INDRAMAYU - Ayatullah, Nichola Michael; Harahap, Muhammad Nasim; Nasution, R. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The quality of the Financial Statement Performance of the Regional Apparatus Work Unit (SKPD) of Indramayu Regency can be influenced by many factors, including good governance and internal control. The more good governance and internal control are implemented, it will improve the quality of the financial statement performance of the Regional Apparatus Work Unit (SKPD) of Indramayu Regency. This study aims to determine the effect of good governance and internal control on the quality of financial statement performance of the Regional Apparatus Work Unit (SKPD) of Indramayu Regency. The research methods used are descriptive and verifiative methods with a quantitative approach. The sample in this study amounted to 100 respondents. The sampling technique uses probability sampling and stratified sampling. The analysis tool used is path analysis with software tools using SPSS 25. The results showed that the picture for good governance and internal control over the quality of the financial statement performance of the Regional Apparatus Work Unit (SKPD) of Indramayu Regency was considered good. Good governance and internal control over the quality of financial statement performance had a significant positive effect of 71.93%, while the influence of other variables that were not studied in this study was 28.07%..